Compliance of procurement and contract Management following Public Procurement Act-2006, Public Procurement Rules-2008 and Standard Tender Documents (STD) in public procurement: A Case studies of some selected procurement contracts of LGED. - Alam, A B M Khorshed (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2024.